Teaching to support children's artistic independence how children's creativity can inform art education - Szekely, George E. (Routledge, Taylor & Francis Group, 2022)
"This engagingly written, research- and practice-based book defines how art teachers can build on students' creative initiatives without depending on adult-imposed lesson plans and school requirements. In doing so, art educator and author George Szekely explores the role of the arts in developing children's creativity and sense of purpose, and reminds readers that students in the art classroom are unique artists, designers, and innovators. Against the backdrop of a school culture that over-emphasizes compliance and standardization, Szekely recognizes the importance of the role of the art teacher in supporting the artistic independence and creative flare that occurs naturally in students of all ages in the classroom. Providing real-life examples of classrooms and schools that work towards championing child artists, this text arms teachers with the skills necessary to listen to their students and support them in presenting their ideas in class. Ultimately, Szekely challenges readers to focus the practice of art teaching on the student's creative process, rather than the teacher's presentation of art. Written for pre-service and in-service art educators, teacher educators, and researchers, Teaching to Support Children's Creativity and Artistic Independence demonstrates that an openness to youthful and inquisitive visual expression inspires a more rewarding learning experience for both teacher and child artists that can support a life-long love of art. George Szekely is Senior Professor and Area Head of Art Education at the University of Kentucky, USA. He is the author of numerous books including Art Teaching, Play and Creativity in Art Teaching, and Art Rooms as Centers for Design Education, all published by Routledge"--